Implementing the 2013 Curriculum on Study Accounting at MA Al Manshuriyah Sukabumi - Iin Khairunnisa; Siska Dwi Yulianti (Universitas Muhammadiyah Mataram, 2018)
The implementation of the 2013 curriculum further educates students to make observations, ask questions and reason on the knowledge being taught. Students are given lessons based on integrated themes in order to have knowledge about the environment, life, and have a strong personal foundation in social life and better creativity. Learning is a process that is able to condition students to achieve or obtain a number of learning experiences in the form of knowledge, skills, social, and basic values that are reflected in the habits of thinking and acting. Accounting is a science that is beneficial to human life. Almost everyone has applied accounting in daily life, such as how to arrange pocket money to be sufficient for a certain period of time or how spending money can be allocated in accordance with the expected shopping needs. This study aims to analyze and describe the effect of applying the 2013 curriculum in the accounting learning process at MA Al Manshuriyah, Sukabumi City. Respondents are teachers who teach at MA Al Manshuriyah, Sukabumi City. Data collection methods are observation, interview, and documentation. Data analysis is data collection, data reduction, and verification. This study found that the effect of applying the 2013 curriculum in the learning process resulted from: a) the learning activities were designed by the teacher so that the learning process could be carried out professionally, b) the learning activities were organized for several activities namely introduction, main activities, and closing. The main activities are divided into three steps (exploration, elaboration, confirmation) which are realized in observing, questioning, collecting data, linking, and communicating.